3(x+6)=4(x+5)=

Simple and best practice solution for 3(x+6)=4(x+5)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x+6)=4(x+5)= equation:



3(x+6)=4(x+5)=
We move all terms to the left:
3(x+6)-(4(x+5))=0
We multiply parentheses
3x-(4(x+5))+18=0
We calculate terms in parentheses: -(4(x+5)), so:
4(x+5)
We multiply parentheses
4x+20
Back to the equation:
-(4x+20)
We get rid of parentheses
3x-4x-20+18=0
We add all the numbers together, and all the variables
-1x-2=0
We move all terms containing x to the left, all other terms to the right
-x=2
x=2/-1
x=-2

See similar equations:

| 1/9y+3=-6 | | x=2/3=8/9 | | 43z=2043z=20. | | 3(x+6=4(x+5) | | -16t^2+155t+105=0 | | -2(z-5)-4=-22 | | (2x-3)(2x+2)=0 | | 0.15s+13.45=13.6 | | 33(2x-4)=18 | | 4x-3=2x+2= | | X-4=5x+11 | | -11z+5z=18 | | 3x+160=2x-195 | | 18=2-4v | | 4/3z=20z= | | 25-3x=38 | | 40=15-9z-2 | | -9.5+0.75h=-9.5 | | Y=-1.5x+5.5 | | 9x-14=5x+58 | | X/58+44/58=x/32+30/32 | | 55=5(3x+-1) | | —14=2x-88 | | (2x-5)+(3x+10)=180 | | P(2400)=650+0.09d | | 4/5x+6=15 | | q/(7/8)=64 | | X/58+44=x/32+30 | | d÷1,000=10 | | 13*x-1=6*x+4 | | -243=-7(10+x) | | a^2-0.25=0 |

Equations solver categories